Enhanced Interleukin 6 Trans-Signaling Modulates Disease Process in Amyotrophic Lateral Sclerosis Mouse Models - Carol Milligan; Dale O. Cowley; William Stewart; Alyson M. Curry; Elizabeth Forbes; Brian Rector; Annette Hastie; Liang Liu; Gregory A. Hawkins (Brain Sciences)
Background/Objectives: Charcot first described ALS in 1869, but the specific mechanisms that mediate the disease pathology are still not clear. Intense research efforts have provided insight into unique neuroanatomical regions, specific neuronal populations and genetic associations for ALS and other neurodegenerative diseases; however, the experimental results also suggest a convergence of these events to common toxic pathways. We propose that common toxic pathways can be therapeutically targeted, and this intervention will be effective in slowing progression and improving patient quality of life. Here, we focus on understanding the role of IL6 trans-signaling in ALS disease processes. Methods: We leveraged unique mouse models of IL6 trans-signaling that we developed that recapitulate the production of active sIL6R in a genotypic and quantitative fashion observed in humans. Given that the SOD1 transgenic mouse is one of the most highly studied and characterized models of ALS, we bred SOD1G93A mice with IL6R trans-signaling mice to determine how enhanced trans-signaling influenced symptom onset and pathological processes, including neuromuscular junction (NMJ) denervation, glial activation and motoneuron (MN) survival. Results: The results indicate that in animals with enhanced trans-signaling, symptom onset and pathological processes were accelerated, suggesting a role in disease modification. Administration of an IL6R functional blocking antibody failed to alter accelerated symptom onset and disease progression. Conclusions: Future work to investigate the site-specific influence of enhanced IL6 trans-signaling and the tissue-specific bioavailability of potential therapeutics will be necessary to identify targets for precise therapeutic interventions that may limit disease progression in the 60% of ALS patients who inherit the common Il6R Asp358Ala variant.